Analisis Pengaruh Kualitas Layanan Website PMB Amikom Purwokerto Menggunakan Metode Webqual 4.0 - Luzi Dwi Oktaviana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In the current era of digital, the role of internet technology is felt to be even greater because almost all business activities in organizations can be carried out through cyberspace. Through the Internet, all the desired information can be obtained easily and quickly. This advantage is of course utilized by universities in improving the quality of education and services through website-based media or websites. As with the University of Amikom Purwokerto, applying for new student registration using a website service that makes the remote registration process easier. In the process of implementing the website in order to always increase user satisfaction, it is necessary to analyze what factors can affect the quality of the website on website services so that it can continue to be improved. The results of this research analysis are seen from the Usability Quality (WEB-U), Information Quality (WEB-IQ), Service Information Quality (WEB-SQ) variables that have a positive influence on the quality of website user services, in this case, User Satisfaction (SUM-US). ). The resulting regression equation is Y = 0.229 + 0.136 X1 + 0.212 X2 + 0.402 X3